MLH1 and MSH2 mismatch repair protein profile using immunohistochemistry in Nepalese colorectal cancer patients (Medical Journal of Indonesia, 2020)
BACKGROUND Hereditary nonpolyposis colorectal cancer, or Lynch syndrome, caused by germline mutations or genetic defects in mismatch repair (MMR) genes (MLH1, MSH2, PMS2, MSH6, and epithelial cellular adhesion molecule), is an autosomal dominant condition accounting for 2–5% of all colorectal carcinomas (CRCs). Reports on MMR loss in many populations are available; however, there are no reports on the frequency of MMR protein expression in Nepalese cohorts. Therefore, this study was aimed to assess the expression profiles of MLH1 and MSH2 protein by immunohistochemistry (IHC) in Nepalese CRC patients. METHODS This retrospective study used archived formalin-fixed paraffin-embedded tissue blocks from 43 Nepalese CRC patients. IHC staining was performed using MLH1 and MSH2 antibodies. IHC scoring analysis was assessed using semiquantitative scoring. RESULTS Of the 43 CRC patients, 8 (18.6%) showed loss of staining for MLH1 antibody, 5 (11.6%) showed loss of staining for MSH2 antibody, and 4 (9.3%) showed loss of staining for both MLH1 and MSH2 antibodies. CONCLUSIONS IHC is a potential screening method of determining the MMR expression profile of Nepalese CRC patients. IHC can be performed in local clinical laboratories to find MMR protein defects in selected cases prior to expensive molecular tests.